Effectiveness of Interactive Education in Improving Knowledge About Reproductive Health at Eskola Secundaria Geral 1912 Dom Boaventura and Colegio Sáo Miguel Arcanjo Same Year 2024 - Texeira, Gonzalo Jose; Owa, Maria Goreti; Blegur, Leny; Yanto, Yosep Uli; Guterres, Dulce Maria; Correia, Helio (Jurnal Kesehatan Komunitas Indonesia, 2024)
Adolescents who face reproductive health issues without adequate support or understanding are likely to experience stress, anxiety and depression, which can affect their overall quality of life. This study aims to analyse the effectiveness of interactive education in improving reproductive health knowledge of high school students at Eskola Secundaria Colegio Sáo Miguel Arcanjo and Eskola Secundaria Geral 1912 Dom Boaventura Same Manufahi Timor-Leste. This study used a quasi-experimental design with a pretest-posttest approach involving two groups of high school students, namely an experimental group from Eskola Secundaria Colegio Sáo Miguel Arcanjo Same that received interactive education and a control group from Eskola Secundaria Geral 1912 Dom Boaventura Same that received traditional teaching methods. Data were collected through a questionnaire that measured various student variables before and after the educational intervention. The results showed that interactive education significantly improved students' reproductive health knowledge. In Eskola Secundaria Colegio Sáo Miguel Arcanjo, 48.6% of students had increased knowledge after the education, compared to 42.9% before the intervention. In contrast, in the control group (Eskola Secundaria Geral 1912 Dom Boaventura), only 11.4% of students achieved adequate knowledge after traditional education, while 88.6% remained in the insufficient knowledge category. In addition, high motivation to learn, good understanding of the material, engagement in discussions and teacher support influenced the success of interactive education. Interactive education was found to be effective in improving reproductive health knowledge among students of Eskola Secundaria Colegio Sáo Miguel Arcanjo, compared to conventional teaching methods. Therefore, a more interactive educational approach that supports active student engagement is recommended to be implemented in reproductive health education programmes in schools.